Muscle mitochondrial energetics predicts mobility decline in well‐functioning older adults: The baltimore longitudinal study of aging. Issue 2 (20th January 2022) - Tian, Qu; Mitchell, Brendan A.; Zampino, Marta; Fishbein, Kenneth W.; Spencer, Richard G.; Ferrucci, Luigi
Abstract: Background: Muscle mitochondrial dysfunction is associated with poor mobility in aging. Whether mitochondrial dysfunction predicts subsequent mobility decline is unknown. Methods: We examined 380 cognitively normal participants aged 60 and older (53%women, 22%Black) who were well‐functioning (gait speed ≥ 1.0 m/s) and free of Parkinson's disease and stroke at baseline and had data on baseline skeletal muscle oxidative capacity and one or more mobility assessments during an average 2.5 years. Muscle oxidative capacity was measured by phosphorus magnetic resonance spectroscopy as the post‐exercise recovery rate of phosphocreatine (kPCr ). Mobility was measured by four walking tests. Associations of baseline kPCr with mobility changes were examined using linear mixed‐effects models, adjusted for covariates. In a subset, we examined whether changes in muscle strength and mass affected these associations by adjusting for longitudinal muscle strength, lean mass, and fat mass. Results: Lower baseline kPCr was associated with greater decline in all four mobility measures (β, p ‐value: (0.036, 0.020) 6‐m usual gait speed; (0.029, 0.038) 2.5‐min usual gait speed; (0.034, 0.011) 6‐m rapid gait speed; (−0.042, <0.001) 400‐m time). In the subset, further adjustment for longitudinal muscle strength, lean mass, and fat mass attenuated longitudinal associations with changes in mobility (Δβ reduced 26–63%). Conclusion: Among initially well‐functioning older adults, worse muscle mitochondrial function predicts mobility decline, and part of this longitudinal association is explained by decline in muscle strength and mass. Our findings suggest that worse mitochondrial function contributes to mobility decline with aging. These findings need to be verified in studies correlating longitudinal changes in mitochondrial function, muscle, and mobility performance. Abstract : Those with low baseline muscle mitochondrial function had greater decline in usual gait speed and greater increase in 400 m walk time than those with high baseline function.